2018
DOI: 10.15252/emmm.201708816
|View full text |Cite
|
Sign up to set email alerts
|

PARP‐1 regulates DNA repair factor availability

Abstract: PARP‐1 holds major functions on chromatin, DNA damage repair and transcriptional regulation, both of which are relevant in the context of cancer. Here, unbiased transcriptional profiling revealed the downstream transcriptional profile of PARP‐1 enzymatic activity. Further investigation of the PARP‐1‐regulated transcriptome and secondary strategies for assessing PARP‐1 activity in patient tissues revealed that PARP‐1 activity was unexpectedly enriched as a function of disease progression and was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 97 publications
3
48
0
Order By: Relevance
“…DSBs cannot be repaired by the HR pathway in BRCA-deficient cells, which forms the basis for synthetic lethality approaches with PARP inhibitors. Moreover, PARP inhibition itself induces HR deficiency by reducing the expression of the E2F1 target genes involved in DNA replication and cell cycle regulation (e.g., PCNA, MCM7, and CCNA2) and HR factors such as BRCA1/2 and RAD51, as shown in prostate and small cell lung cancer (Byers et al 2012;Schiewer et al 2018). A contingency pathway for DSB repair, NHEJ, which is functional throughout the cell cycle, is thought to compensate for inactive HR in PARP inhibitor-treated cells.…”
Section: Amplifying Genomic Instability With Parp and Parg Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…DSBs cannot be repaired by the HR pathway in BRCA-deficient cells, which forms the basis for synthetic lethality approaches with PARP inhibitors. Moreover, PARP inhibition itself induces HR deficiency by reducing the expression of the E2F1 target genes involved in DNA replication and cell cycle regulation (e.g., PCNA, MCM7, and CCNA2) and HR factors such as BRCA1/2 and RAD51, as shown in prostate and small cell lung cancer (Byers et al 2012;Schiewer et al 2018). A contingency pathway for DSB repair, NHEJ, which is functional throughout the cell cycle, is thought to compensate for inactive HR in PARP inhibitor-treated cells.…”
Section: Amplifying Genomic Instability With Parp and Parg Inhibitorsmentioning
confidence: 99%
“…Hypoxia induces reduction in binding of the activating transcription factor E2F1 to the BRCA1 promoter, resulting in reduced BRCA1 expression (Bindra et al 2005). PARP inhibition also reduces E2F1 genomic binding and expression of the E2F1 target genes (Byers et al 2012;Schiewer et al 2018) and may thereby synergize with hypoxic effects induced by antiangiogenic agents. A successful example of such a synergy is given by the combination of olaparib with the pan-VEGF inhibitor cediranib, which increased median progression-free survival from 9 to 17.7 mo compared with olaparib alone in platinum-sensitive ovarian cancer (Liu et al 2014).…”
Section: Inhibitors Of Transcription Regulators and Epigenetic Modifiersmentioning
confidence: 99%
“…PARP-1 has also been involved in prostate cancer progression, as PARP-1 expression in the nuclear matrix increases with tumor invasiveness [62]. Finally, both enzymatic activity and transcriptional regulatory functions of PARP-1 were reported to be elevated as a function of prostate cancer progression, independently of DNA double strand breaks, but through enhancement of E2F1-mediated induction of DNA repair factors involved in HR [63]. Elevated PARP-1 mRNA and protein are associated with poor prognosis in gastric cancer [64,65]; PARP-1 mRNA is elevated in colon carcinoma when compared to adenoma [66]; PARP-1 gene expression is associated with lymph node spread of malignant pleural mesothelioma [67]; and PARP-1 mRNA and protein are elevated in endometrial adenocarcinoma [68].…”
Section: High Activity Of Parp-1 In Tumor Development and Progressionmentioning
confidence: 99%
“…Consistently, emerging works suggest that inhibition of PARP1 induces DNA damage-dependent pro-inflammatory response 36,37,[40][41][42] . These observations suggested that activation of PARP-1 not only enhances DNA repair 43 but also triggers an anti-inflammatory signaling cascade [36][37][38][39] .…”
mentioning
confidence: 93%